2007
DOI: 10.1227/01.neu.0000249257.16912.aa
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Mounted Miniature Robotic Guidance for Pedicle Screw and Translaminar Facet Screw Placement

Abstract: These results verify the system's accuracy and support its use for minimally invasive spine surgery in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 40 publications
4
65
0
3
Order By: Relevance
“…From a practical standpoint, these new systems are too complicated to be used widely, whereas the accuracy remains suboptimal and highly dependent on multiple variables [24]. However, the technology continues to evolve, increasing its overall ability.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical standpoint, these new systems are too complicated to be used widely, whereas the accuracy remains suboptimal and highly dependent on multiple variables [24]. However, the technology continues to evolve, increasing its overall ability.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the device and related surgical techniques have been described previously [7,10,12,14]. A CT scan using 1 mm cuts was obtained preoperatively in all patients for the surgery planning using the proprietary robotic software (Fig.…”
Section: Robotic Guidance System and Surgical Techniquesmentioning
confidence: 99%
“…The need for improved accuracy and consistency in pedicle screw placement has led to the development of various new techniques, such as computer navigated and robotic-assisted spine surgery [7][8][9][10][11]. There are now reports showing that these newer techniques have improved the accuracy of pedicle screw placement [5,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 illustrates the variety of cadaveric studies that have been performed and their characteristics. 18,19,21,[25][26][27]38,40 Whereas many published studies consisted of 1-2 cadavers, Togawa et al 42 reported on the placement of lumbosacral pedicle screws, translaminar facet screws, and was assessed separately; they had all been placed successfully, with an overall average deviation of 1.03 ± 0.59 mm. In the translaminar facet instrumentation surgery, the overall average K-wire deviation was 1.05 ± 0.56 mm.…”
Section: Cadaveric Studies Of Robot-assisted Spine Surgerymentioning
confidence: 99%